Encyclopedia: Nature-Based Learning Initiative to Enhance Students' Critical Thinking - Audrey Louise Makatita; Jeany Tomatatala; Mayesti Rambu Jati; Mia Fransiska mangi Dimu (Postgraduate, University of Mataram, 2025)
This study aims to implement a Nature-Based Learning Initiative as an innovative solution to enhance students' critical thinking skills at SD Inpres Hiliwuku, East Sumba. The school faces significant challenges due to its remote location and a lack of electricity and internet access, which restricts conventional teaching methods. This approach utilizes the surrounding natural environment as a